COMPILATION OF HEDGING SHARE PORTFOLIO BASED ON PCA ON INDONESIA'S LQ45 INDEX - sunarto wage; Nanda Harry Mardika; Suvianto Wangdra (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2023)
Stock investing is a risky subject that requires hedging, but this is rarely questioned in the Indonesian stock index. The goal of this study is to create a stock portfolio using principal components to develop orthogonal components in the Indonesian LQ45 index for hedging purposes. The research method used time series over a five-year period from 2017 to 2021. From different cumulative returns, daily returns, and risk profiles, four components were created with total extracted variance of 84% and KMO of 90%. With a 95% confidence interval, the results are also statistically different. The hypothetical portfolio constructed from the four components produced an excellent hedge profile based on the sharpe ratio, with negative stock performance counterbalanced by positive stock performance.